A medieval woman's companion : women's lives in the European Middle Ages - Morrison, Susan Signe, 1959- (Oxbow Books, 2016)
What have a deaf nun, the mother of the first baby born to Europeans in North America, and a condemned heretic to do with one another? They are among the virtuous virgins, marvellous maidens, and fierce feminists of the Middle Ages who trail-blazed paths for women today. Without those first courageous souls who worked in fields dominated by men, women might not have the presence they currently do in professions such as education, the law, and literature. Focusing on women from Western Europe between c. 300 and 1500 CE in the medieval period and richly carpeted with detail, A Medieval Woman's Companion offers a wealth of information about real medieval women who are now considered vital for understanding the Middle Ages in a full and nuanced way. Short biographies of 20 medieval women illustrate how they have anticipated and shaped current concerns, including access to education; creative emotional outlets such as art, theatre, romantic fiction, and music; marriage and marital rights; fertility, pregnancy, childbirth, contraception and gynecology; sex trafficing and sexual violence; the balance of work and family; faith; and disability. Their legacy abides until today in attitudes to contemporary women that have their roots in the medieval period. The final chapter suggests how 20th and 21st century feminist and gender theories can be applied to and complicated by medieval women's lives and writings. Doubly marginalised due to gender and the remoteness of the time period, medieval women's accomplishments are acknowledged and presented in a way that readers can appreciate and find inspiring. Ideal for high school and college classroom use in courses ranging from history and literature to women's and gender studies, an accompanying website with educational links, images, downloadable curriculum guide, and interactive blog will be made available at the time of publication.